AMENDMENT OF SOIL WITH WEATHERED POULTRY MANURE, COW DUNG AND SAWDUST FOR THE MANAGEMENT OF MELOIDOGYNE SPP. AND OTHER NEMATODES IN OKRA - ADEKUNLE , O.K. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Two separate, but identical greenhouse experiments and a field experiment were conducted to evaluate weathered poultry manure. cow dung and sawdust applied as soil amendment singly at 1.5 t /ha and 3.0 t /ha in the management of Meloidogyne spp. and other nematodes on okra cv. 47-4. Under greenhouse conditions, weathered poultry manure applied at 3.0 t /ha to nematode-infected okra resulted in taller plants with higher leaf number and lower root galling in comparison with other plants. This treatment also significantly reduced the soil population of Meloidogyne spp. second stage juveniles than other treatments. In the field infested with Meloidogyne spp. and other genera of plant parasitic nematodes, poultry manure-amended plants were the least galled, followed by plants amended with cow dung and sawdust. The highest fruit yield was recorded from plants amended with poultry manure. Lowest percentage Meloidogyne spp. population increase (12.6 %) was recorded in soil amended with weathered poultry manure at 3.0 t / ha, followed by soil amended with cow dung (17.8%) and sawdust (33.9%). The percentage change in soil populations of Paratylenchus spp. Paratylenchus spp. and Hoplolaimus spp. followed a similar trend. Thus, application of weathered poultry manure at the rate of 3.0 t /ha to nematode-infested okra garden may have practical benefits for management of the pest.